2020
DOI: 10.18203/2349-2902.isj20201378
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome of hepatolithiasis: Nepalese experience

Abstract: Background: Hepatolithiasis is a rare disease with high rate of treatment failure and recurrence. This study aims to review the burden, management and outcome from an endemic region.Methods: A retrospective review of database of patients with hepatolithiasis managed surgically from 2015 to 2019 was performed. Diagnosis was based on the clinical findings and radiological investigations. Demographic data, clinical presentation, extent of disease and type of surgical management were evaluated. The outcome measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Even though cases of hepatolithiasis are common in South Asia compared to western world, rarely cases are reported from Nepal. 2 A retrospective study conducted in a tertiary care centre of Nepal showed 0.34% prevalence of hepatolithiasis among biliary surgeries 7 . Hepatolithiasis has variety of presenting complains ranging from abdominal pain to cholangitis-like features or it can be found incidentally as reported in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Even though cases of hepatolithiasis are common in South Asia compared to western world, rarely cases are reported from Nepal. 2 A retrospective study conducted in a tertiary care centre of Nepal showed 0.34% prevalence of hepatolithiasis among biliary surgeries 7 . Hepatolithiasis has variety of presenting complains ranging from abdominal pain to cholangitis-like features or it can be found incidentally as reported in our case.…”
Section: Discussionmentioning
confidence: 99%
“…It is similar to that observed by Pandit N et al in their study. 8 This early age at presentation of hepatolithiasis may be because of low socioeconomic conditions, malnutrition and recurrent subclinical infections of the biliary tree. 1 Hepatolithiasis was found to occur more frequently in left liver (50%) in our study.…”
Section: Discussionmentioning
confidence: 99%